Investigation into EHR data coverage in the All of Us Research Program via linkage to health insurance claims - Yuyang Yang; Kelsey Rodriguez; Javier Ezcurra; Romain Bogaerts; Andres Corrada-Emmanuel; Lew Berman; Melissa Basford; Abel Kho (PLoS ONE, 2026)
In 2020, the All of Us (AoU) Research Program Data Completeness Task Force identified several challenges in the state of program health data, including the high likelihood that Electronic Health Record (EHR) data from recruitment institutions is missing a significant portion of care received by participants. To improve data availability, the AoU Data Completeness Task Force recommended efforts to work with industry partners to better understand the degree of missingness within AoU EHR data, with an initial focus on claims data. In this study we describe efforts from AoU’s collaboration with Swoop, a commercial analytics company holding health insurance claims data for over 80% of Americans, to assess the degree to which health insurance claims data can fill out the complete picture of care received by AoU participants. Using record linkage to link between individual participant AoU EHR data and their respective insurance claims, we quantitatively assess the amount of missing health data in both Swoop claims data and AoU EHR data over a decade long sample, identifying trends in data missingness based on participant characteristics. Our analysis demonstrates that AoU would greatly benefit from ingestion of claims data, gaining an estimated 16 million (90 per person) unique diagnosis codes, 17.8 million (99 per person) unique procedure codes, and 9.4 million (53 per person) unique drug codes through linkage to claims data.